Tindak Tutur Ilokusi dalam Video “Membedah 100 Hari Kabinet Prabowo” di Kanal YouTube Raymond Chin: Kajian Pragmatik - Alifya Aenatul Nabila; Athia Az-zakia Anwar; Hidayatul Afifah; Nur Saidah; Qurrota Ayu Neina; Tommi Yuniawan (Institut Nalanda, 2025)
This research discusses the use of illocutionary speech acts in videos uploaded on Raymond Chin's YouTube channel. The main purpose of this research is to identify and analyze the types of illocutionary speech acts that appear, such as assertive, commissive, directive, expressive, and declarative. This research uses a descriptive qualitative approach with data collection techniques in the form of listening and recording, and data analysis through agih and padan methods. Assertive speech acts are used to convey the speakers' opinions and beliefs about social and political situations. Directive speech acts function to invite the audience to engage and think critically. Declarative speech acts are used to state facts or emphasize the speaker's views. Meanwhile, commissive speech acts show the speaker's ability or intention in responding to the topic being discussed, and expressive speech acts show the speaker's emotions, both in the form of appreciation and criticism. Raymond Chin utilizes various illocutionary strategies to deliver criticism in an analytical way, build audience engagement, and express his opinions politely and effectively in the context of digital communication.